Neonatal Sepsis Episodes and Retinopathy of Prematurity in Very Preterm Infants. - Glaser, Kirsten; Härtel, Christoph; Klingenberg, Claus; Herting, Egbert; Fortmann, Mats I.; Speer, Christian P.; Stensvold, Hans J.; Huncikova, Zuzana; Rønnestad, Arild E.; Nentwich, Martin M.; Stahl, Andreas; Dammann, Olaf; et al. (JAMA Network Open, 2024)
IMPORTANCE: Retinopathy of prematurity (ROP) is a major morbidity of preterm infants causing visual impairment, including blindness, for which timely treatment is vital and prevention is key. Increasing evidence suggests that exposure to neonatal sepsis contributes to ROP development. OBJECTIVE: To investigate the association between neonatal sepsis and ROP in 2 large-scale cohorts of preterm infants born at less than 29 weeks' gestation. DESIGN, SETTING, AND PARTICIPANTS: This retrospective cohort study was conducted using data from the German Neonatal Network (GNN) and Norwegian Neonatal Network (NNN). The GNN involves 68 and the NNN includes 21 level III neonatal intensive care units. Participants were infants born at a gestation of 22 weeks and 0 days to 28 weeks and 6 days and enrolled in the GNN between January 1, 2009, and December 31, 2022, and NNN between January 1, 2009, and December 31, 2018. Data were analyzed from February through September 2023. EXPOSURE: Single or multiple episodes of culture-proven sepsis. MAIN OUTCOMES AND MEASURES: Any ROP and treatment-warranted ROP. RESULTS: Among 12 794 infants in the GNN (6043 female [47.2%] and 6751 male [52.8%]; mean [SD] gestational age, 26.4 [1.5] weeks) and 1844 infants in the NNN (866 female [47.0%] and 978 male [53.0%]; mean [SD] gestational age, 25.6 [1.5] weeks), the mean (SD) birth weight was 848 (229) g and 807 (215) g, respectively. Any ROP was present in 6370 infants (49.8%) in GNN and 620 infants (33.6%) in NNN, and treatment-warranted ROP was present in 840 infants (6.6%) in GNN and 140 infants (7.6%) in NNN. In both cohorts, there were increasing rates of treatment-warranted ROP with each sepsis episode (no sepsis: 572 of 10 658 infants [5.4%] in GNN and 85 of 1492 infants (5.7%) in NNN; 1 episode: 190 of 1738 infants in GNN [10.9%] and 29 of 293 infants [9.9%] in NNN; 2 episodes: 53 of 314 infants in GNN [16.9%] and 13 of 49 infants [26.5%] in NNN; 3 episodes: 25 of 84 infants [29.8%] in GNN and 3 of 10 infants [30.0%] in NNN). After adjusting for multiple confounders in the GNN dataset, the number of sepsis episodes was associated with ROP and treatment-warranted ROP compared with 0 episodes (1 episode: adjusted odds ratio [aOR], 1.44 [95% CI, 1.27-1.63]; P < .001 and OR, 1.60 [95% CI, 1.31-1.96]; P < .001, respectively; 2 episodes: OR, 1.81 [95% CI, 1.35-2.42]; P < .001 and OR, 2.38 [95% CI, 1.68-3.37]; P < .001, respectively; 3 episodes: OR, 4.39 [95% CI, 2.19-8.78]; P < .001 and OR, 3.88 [95% CI, 2.29-6.55]; P < .001, respectively). These associations were confirmed for any ROP by propensity score matching (for example, the aOR with propensity score matching was 1.76 [95% CI, 1.54-2.02]; P < .001 for 1 episode vs 0 episodes and 1.58 [95% CI, 1.12-2.22]; P = .007 for 3 episodes vs 0 or 1 episode). In the NNN dataset, surgical NEC was associated with treatment-warranted ROP (multivariable analysis: aOR, 3.37 [95% CI, 1.78-6.37]; P < .001). CONCLUSIONS AND RELEVANCE: This study found that in the large-scale GNN cohort, recurrent culture-proven sepsis was associated with ROP and treatment-warranted ROP in infants born at less than 29 weeks.
EVALuna2:584636